A pesquisa em serviço social: a vinculação da investigação e da intervenção na prática profissional do assistente social - Fontana, Maria Inês (2010)
The general objective of this thesis is to comprehend the liaison between academic research and professional practice of the Social Assistant during its daily work in the various actuation areas. This research subjects were professionals who work on public and private institutions and, concomitantly, were trainee supervisors of students from University of Social Services of Bauru, in 17 cities inside the 7th Administrative region of São Paulo state. The research took quantitative and qualitative data from the answers of 63 people, who answered a list of specific questions. Between these subjects were selected eight professionals who participated of a focal group. The collected data showed that the Social Assistants recognize the relevance of the research on their daily work, point it as a need for a better qualification of the professional work and describe it as a fundamental instrument of reality knowledge as well as the professional demand, attributing it relevance on the directionally professional intervention. Also the research was qualified by the subjects as one way to maintain the professional competence and job on daily work; responsible to forward the professional projects on the direction of the ethic-politic accomplishment inside the profession. The subjects also detached that having a distinguished perspective, this research can be used as a strength way of population struggle, as a possibility of social practices transposition and, per its democratic sign, to mark the subjects take part. They still related that the category uses the research only as an insipient way, attributing its non usage on the professional practice to the leak of habit and research method knowledge, behind the difficulty of a systemization and to the poor tradition of research on the Social Service. They explained that the alteration of this scenario will be possible per a collective construction which must be stimulated and effectuated by the representative agencies (CRESS, CFESS e ABPESS) which should happen during the studies and be present on the agenda and roll of continuous capacitating of theses professionals. Finally it was evident the humility feeling by the subjects and the conception that the current scenario must be improved